Impact of tacrolimus variability on pediatric heart transplant outcomes. (13th August 2021) - Sirota, Megan; Heyrend, Caroline; Ou, Zhining; Masotti, Susan; Griffiths, Eric; Molina, Kimberly
Abstract: Background: Tacrolimus is a narrow therapeutic index drug, requiring consistent levels to maximize transplant success while reducing adverse effects. Elevated tacrolimus level variability (ETLV) is associated with poor outcomes in both pediatric and adult solid organ transplant recipients. We sought to describe the prevalence of ETLV and identify associations with patient‐specific factors and poor outcomes. Methods: Tacrolimus levels were evaluated from 118 patients at our single center. As a marker of variability, standard deviations (SD) were calculated for each patient from their entire tacrolimus level data set (global SD), and 1–2 years and 1–5 years post‐HT (prediction window SDs). SD ≥3 denoted ETLV. Results: There was large variability in tacrolimus levels (median global SD 3.1; IQR 2.3, 4; SD ≥3, n  = 64, 54%). Patients with elevated SD (≥3) vs lower SD (<3) were more likely to have poor outcomes including rejection (73% vs 46%), cardiac allograft vasculopathy (CAV, 22% vs 9%), and death (20% vs 6%). The prediction window analysis noted ETLV was associated with a 40% greater risk of CAV, re‐HT, or death ( p  = .024) and increasing age at transplantation was associated with a 12% increase in the risk of rejection ( p  = <.001) and a 19% increase in the risk of a composite event ( p  = .021). Conclusion: ETLV is prevalent in the pediatric HT population with increased frequency of poor outcomes in those with SD ≥3. ETLV is an easily accessible marker with which to risk‐stratify patients.